Examples of low-level aerial surveys conducted in Africa from 1968 to 1979: One firm's experience - Watson, R.M.; Tippet, C.I. (International Livestock Centre for Africa, 1981)
Discusses the role of light aircraft remote sensing methods using examples of different surveys carried out by the Resource Management and Research (RMR) firm in nine African countries and over international waters from 1968 to 1979.